An injectable peptide hydrogel with excellent self-healing ability to continuously release salvianolic acid B for myocardial infarction. (July 2021) - Chen, Rui; Zhu, Chenqi; Xu, Liu; Gu, Yi; Ren, Shujing; Bai, Hua; Zhou, Qin; Liu, Xin; Lu, Shengfeng; Bi, Xiaolin; Li, Weidong; Jia, Xiaobin; et al.
Abstract: Drug-loaded hydrogels can improve blood supply and inhibit extracellular matrix degradation after myocardial infarction. However, due to the continual dynamic motion of cardiac tissue, the hydrogel structure cannot be reconstructed in time, causing accelerated degradation and drug burst release. Here, a novel, superior, self-healing elastin-mimic peptide hydrogel (EMH) was fabricated for the local delivery of salvianolic acid B (SaB). The self-healing ability of EMH is enhanced by SaB-loaded polydopamine nanoparticles (SaB-PDA). In vitro, the pre-hydrogel (SaB-PDA/pre-EMH) is endowed with excellent biocompatibility and a low viscosity, making it suitable for intramyocardial injection. Once injected into the myocardial infarction (MI) region, SaB-PDA/pre-EMH can form SaB-PDA/EMH with great mechanical strength under the action of upregulated transglutaminase (TGase) in heart tissue post-MI. The superior self-healing ability of SaB-PDA/EMH allows for an increase in retention time in the beating ventricular wall. Therefore, with long-term release of SaB, SaB-PDA/EMH can inhibit ventricular remodeling and promote angiogenesis for MI treatment.